Pharmacokinetic characteristics of monoclonal antibodies and importance in the process of biosimilar registration - Pejčić, Zorica (Archives of Pharmacy, 2022)
Monoclonal antibodies (mAbs) possess some unique pharmacokinetic properties as a consequence of their structure and function, making the development of mAbs substantially different from that of conventional drugs. After s.c. or i.m. application mAbs are absorbed through the lymphatic system by the convection process. Distribution to tissues is part of the elimination process, passage through cell membranes is limited by molecular mass and polarity, and a significant amount of mAbs is found in vascular and interstitial fluid. Despite a small volume of distribution, sufficient mAb concentrations are reached in target organs due to receptor-mediated uptake. For elimination of mAbs liver and kidneys are not considered essential, as mAbs are eliminatied through (a) nonspecific cell uptake followed by proteolytic degradation or (b) target mediated elimination, through interaction between the Fab region of the mAb and its target site. Long elimination half-life of mAbs is due to neonatal Fc receptor recycling, thus preventing mAbs degradation. Of all registered mAbs, so far only 6 have their biosimilars. An essential part of the mAb biosimilar development program, are comparative pharmacokinetic studies. These studies are designed to confirm similar pharmacokinetic profile of biosimilar with its reference mAt, in terms of both resorption and elimination. The design of these studies depends, among other factors, on the pharmacokinetic properties of the mAb, such as target mediated elimination, long elimination half-life, nonlinear pharmacokinetics, differences in pharmacokinetics between healthy subjects and patients, pharmacokinetic variability, changes in mAb distribution and elimination due to formation of anti-mAb antibodies.